The Impact of KIR Polymorphism on the Risk of Developing Cancer: Not as Strong as Imagined? - Augusto, Danillo G. (Frontiers in Genetics, 2016)
The polymorphism of killer cell immunoglobulin-like receptors (KIR) has been associated with several diseases, including infection, autoimmunity and cancer. KIR molecules are a family of receptors expressed on the surface of natural killer cells (NK), frontline defense of innate immunity against microorganisms and neoplastic cells. Some studies have shown conflicting results concerning the role that KIR polymorphism plays in tumor susceptibility, particularly in leukemia and lymphoma. Interestingly, the presence of HLA ligands is sometimes strongly associated with several types of cancer and apparently is not related with their interaction with KIR. This manuscript briefly reviews the uncommon polymorphism of KIR and critically summarizes the recent findings with regards of the importance of KIR variation for cancer susceptibility.